ACTION PLAN OF THE GOVERNOR OF DKI JAKARTA IN FACING CLIMATE CHANGE AND ITS IMPACT - William Ciputra (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2022)
Abstract This journal aims to examine more deeply the Jakarta Governor's action plan in dealing with climate change and its impact on life. In addition, this journal will also examine the international legal framework that deals with climate change and identify the role of international human rights in climate change issues. This journal begins by identifying the basis of international law, the development of international law, and looking at the character and nature of the framework. This study seeks to identify the role of international human rights law in closing the gaps left by the climate change framework. This research was conducted by examining secondary data from relevant books, journals, and published documents. There are several findings from this study. First, the current international climate change framework is insufficient to address the problem of climate change and its adverse effects. Second, there are many challenges that the Government of Jakarta must face in implementing an action plan to deal with climate change in order to make Jakarta a city capable of dealing with the impacts of climate change. Keywords:Climate change; The role of the Governor of Jakarta; Human rights